Écriture créative et plaisir d’apprendre - Vanasse, Geneviève-Gaël; Noël-gaudreault, Monique (Didáctica. Lengua y Literatura, 2004)
This article aims to suggest a solution to the problem of the quality of writing language, in Quebec, for 17-19 years old students. First, it seems important to teach writing as a recursive process; them, it seems important to motivate learners for learning written language; eventually to stimulate creativity as a motivation factor. In the second part, we present didactical strategies focus on the writing workshop’s motivation.